Three-dimensional inverse dynamics linked segment model in swimming - Allison, J.; Ibrahim, R.; Grimshaw, P.; Kelso, R.; Elipot, M. (ISBS Proceedings Archive (Michigan), 2021)
This study aimed to produce a three-dimensional (3-D) inverse dynamics linked segment model capable of utilising kinematic data of a subject simulating front crawl to determine joint rotations and moments. This model is intended to address the current gap in swimming performance literature concerning the measurement of dynamic loads acting on an athlete during swimming. Joint moments derived from this model are to be used to specify actuator requirements for a biomimetic robotic system which will then be used to replicate human swimming technique